Old clothes - Nunn, Daniel (Chicago, Ill Heinemann Library, 2012)
This book describes simple crafts that can be made using old clothing
A gift from book Africa
Industries
1 2 13 15
Keywords: Clothing and dress -- Environmental aspects -- Juvenile literature; Clothing and dress -- Environmental aspects; Clothing and dress